Acute type A aortic dissection – a review. (2nd January 2020) - Gudbjartsson, Tomas; Ahlsson, Anders; Geirsson, Arnar; Gunn, Jarmo; Hjortdal, Vibeke; Jeppsson, Anders; Mennander, Ari; Zindovic, Igor; Olsson, Christian
Abstract: Acute type A aortic dissection (ATAAD) is still one of the most challenging diseases that cardiac surgeons encounter. This review is based on the current literature and includes the results from the Nordic Consortium for Acute Type-A Aortic Dissection (NORCAAD) database. It covers different aspects of ATAAD and concentrates on the outcome of surgical repair. The diagnosis is occasionally delayed, and ATAAD is usually lethal if prompt repair is not performed. The dynamic nature of the disease, the variation in presentation and clinical course, and the urgency of treatment require significant attentiveness. Many surgical techniques and perfusion strategies of varying complexity have been described, ranging from simple interposition graft to total arch replacement with frozen elephant trunk and valve-sparing root reconstruction. Although more complex techniques may provide long-term benefit in selected patients, they require significant surgical expertise and experience. Short-term survival is first priority so an expedited operation that fits in with the surgeon's level of expertise is in most cases appropriate.